Safety evaluation method of tubing strings in high-pressure, high-temperature and high-yield gas wells based on FIV analysis. (February 2021) - Guo, Xiaoqiang; Liu, Jun; Dai, Liming; Huang, Liang; Wei, Anchao; Fang, Dake; Zeng, Linlin
Highlights: A flow-induced nonlinear vibration (FINV) model of tubing string in 3H gas wells is established. The buckling stability and strength damage evaluation methods of tubing string are proposed. The failure mechanism of tubing string in 3H gas wells is elucidated, and the safety control methods of field tubing string are proposed. The research results provide a theoretically method for safety evaluation of tubing string in 3H gas wells. Abstract: In view of the failures of tubing string caused by the flow-induced nonlinear vibration (FINV) in high-pressure, high-temperature and high-yield (3H) gas wells, a FINV model of tubing string is established using micro-finite element and energy methods, as well as Hamilton variational principle, and verified by a similar experiment of tubing vibration. Moreover, in order to effectively evaluate the safety of the tubing string, the buckling stability and strength damage evaluation method of tubing string are proposed. Thus, the influences of production rate, inclination angle, well section length, and centralizer position on the tubing string safety were systematically analyzed. The failure mechanism of tubing string in 3H gas wells is elucidated, and the safety control methods of field tubing string are proposed; which suggest that, firstly, with the increase of production rate, the safety of the tubing string decreases, and there exists a sudden value, which can be determined using the proposed analysis method, such that the field production allocation should be far away from the sudden production rate. Secondly, in the well trajectory design, the vertical section length should be reduced, while that of kick-off section and the angle of stable inclined section should be increased. Thirdly, there is an optimal position for the centralizer in the field, which is related to the well structure, downhole tool size, etc. and should be determined by the proposed analysis method to enable the design of the centralizer on-site. The research results provide a theoretically method for safety evaluation and practically sound approach for effectively improving the service life of tubing string in 3H gas wells.